Anemia en lactantes menores de seis meses que recibieron suplemento de hierro Ventanilla 2018-2019 - Norabuena Lock, Fabiola Ximena (2020)
ABSTRACT Objective: To determine the influence of the drop iron supplementation program on the anemia of infants under 6 months of age treated at the Márquez Health Center between 2018 and 2019. Methodology: Observational, quantitative, analytical study with a comparative cross-sectional design of prevalences before and after the intervention. The study population was 293 six-month-old children, treated at the Márquez Health Center during 2018 and 2019. Data collection was based on medical records, CRED records and the establishment's iron supplementation record. Data processing and analysis was performed in the SPSS 25 program. The confidentiality of the data and the request for permission from the institution were respected. Results: The frequency of anemia before the supplementation program was 43%, while at term it was 17.4%, the majority of infants were women, 99% began preventive iron drop supplementation at five months, the average birth weight was of three kilos and two of them less than 2,500 grams, the majority due to eutocic delivery and 10% due to caesarean section. Mothers had anemia in 15%, most of them without finishing high school. Iron supplementation was a protective factor for anemia (OR: 0.27) and a 95% CI [0.19-0.40], with a highly significant association (Chi square 45.53 associated with a pV < 0.0001). Conclusion: It was found that supplementation with iron drops acts as a protective factor against anemia in infants, generating 72% protection.